Demographic Characteristics Associated With Adolescent Receipt of Provider E-Cigarette Screening and Advice and the Impact on Harm Perception - John S. Acosta-Peñaloza, MS; Karen W. Geletko, MPH; Jon Mills, PhD (AJPM Focus)
Introduction: The growing prevalence of E-cigarette use among adolescents is alarming because it increases the probability of persistent tobacco use and addiction to nicotine. Healthcare providers are in a unique position to influence their patients’ use of E-cigarettes. The purpose of the study is to determine the frequency at which providers screen adolescents for E-cigarette use and advise against use during healthcare visits. The study also examines associations between provider intervention and adolescent harm perception. Methods: Using data from the 2021 National Youth Tobacco Survey, the authors examined provider E-cigarette screening and advice to not use from 16,910 participants who self-reported receiving medical care within the preceding year. Multivariable logistic regression models were used to assess whether the odds of provider intervention varied by age, sex, and race/ethnicity and whether receiving provider intervention was associated with a likelihood for harm perception. Results: Provider intervention was more likely among those aged 13–18 years, who are male, and who are White and/or non-Hispanic (p<0.001). The authors found no association between provider intervention and increased harm perception of E-cigarettes; however, provider intervention was associated with the belief that E-cigarettes are equally or more addictive than cigarettes (p<0.0001). Conclusions: Study findings emphasize the significance of addressing disparities in E-cigarette use and healthcare provider intervention among minority adolescents, underscoring the need for healthcare providers to be thorough in screening for E-cigarette use and providing appropriate cessation support.